2012
DOI: 10.1016/s1473-3099(12)70051-8
|View full text |Cite
|
Sign up to set email alerts
|

Switching children previously exposed to nevirapine to nevirapine-based treatment after initial suppression with a protease-inhibitor-based regimen: long-term follow-up of a randomised, open-label trial

Abstract: Background Protease inhibitor (PI)-based therapy is recommended as first-line treatment for HIV-infected infants exposed to nevirapine prophylaxis. However, long-term use poses adherence challenges, is associated with metabolic toxicities, limits second-line options, and is costly. We report long-term outcomes of switching nevirapine-exposed children to nevirapine-based therapy after effective suppression of virus replication on a PI-based regimen. Methods At one site in Johannesburg, South Africa, 195 nevir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…The Nevirapine Resistance Study (NEVEREST), a randomized trial of switching NVP‐exposed infants from suppressive LPV/r‐ to NVP‐based ART (after at least 3 months of VL < 400 copies/ml), showed that this strategy can be successful in infants without evidence of transmitted NVP resistance on conventional testing 64, 197. Children switched to NVP had less long‐term dyslipidaemia and subcutaneous fat loss 112.…”
Section: When To Switch Resistance Testing and Second And Subsequentmentioning
confidence: 99%
“…The Nevirapine Resistance Study (NEVEREST), a randomized trial of switching NVP‐exposed infants from suppressive LPV/r‐ to NVP‐based ART (after at least 3 months of VL < 400 copies/ml), showed that this strategy can be successful in infants without evidence of transmitted NVP resistance on conventional testing 64, 197. Children switched to NVP had less long‐term dyslipidaemia and subcutaneous fat loss 112.…”
Section: When To Switch Resistance Testing and Second And Subsequentmentioning
confidence: 99%
“…Special note: The randomized control trial supporting the use of this approach (148,161) defined virological suppression as a viral load ≤400 copies/mm 3 , with the goal of identifying the children who are more likely to be able to safely substitute LPV/r with NVP. The use of a higher viral load cut-off for determining virological suppression has not been studied in the context of this strategy.…”
Section: First-line Art For Children Younger Than Three Years Of Agementioning
confidence: 99%
“…A recent randomized clinical trial (148,161) and an ongoing randomized clinical trial (162) have evaluated a strategy in which LPV/r is started and later substituted with an NNRTI (NVP or EFV). Such PI-sparing strategies aim to reduce exposure to LPV/r, offer an easier approach to maintaining treatment and preserve PI-based therapy for second-line ART.…”
Section: Feasibility Of Lpv/r In Resource-limited Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching suppressed children from LPV/r to NVP for those <3 years or EFV for those >3 years resulted in sustained viral suppression in the Nevirapine Resistance Study (NEVEREST) studies. [20,21] Although switching to EFV in children >3 years and to NVP in those <3 years was successful in some instances, currently infants failing prevention of mother-to-child transmission (PMTCT) have prolonged NNRTI exposure for at least 6 weeks, rather than only a single dose as in NEVEREST, thus increasing the risk of subsequent significant NNRTI resistance. In NEVEREST-2, failure occurred more often in children with baseline NNRTI resistance (plasma RNA >1 000 copies/mL) when switched to NVP than in those remaining on LPV/r (22% v. 10%; p=0.009).…”
Section: Rationale For the Current National First Regimenmentioning
confidence: 99%